Safety and efficacy of allogeneic hematopoietic stem cell transplant after PD-1 blockade in relapsed/refractory lymphoma - Merryman, Reid W.; Kim, Haesook T.; Zinzani, Pier Luigi; Carlo-Stella, Carmelo; Ansell, Stephen M.; Perales, Miguel-Angel; Avigdor, Abraham; Halwani, Ahmad S.; Houot, Roch; Marchand, Tony; Dhedin, Nathalie; Lescaut, Willy; et al. (Blood, 2017)
Anti–programmed cell death protein 1 (PD-1) monoclonal antibodies are being increasingly tested in patients with advanced lymphoma. Following treatment, many of those patients are likely to be candidates for allogeneic hematopoietic stem cell transplant (HSCT). However, the safety and efficacy of HSCT may be affected by prior PD-1 blockade. We conducted an international retrospective analysis of 39 patients with lymphoma who received prior treatment with a PD-1 inhibitor, at a median time of 62 days (7-260) before HSCT. After a median follow-up of 12 months, the 1-year cumulative incidences of grade 2-4 and grade 3-4 acute graft-versus-host disease (GVHD) were 44% and 23%, respectively, whereas the 1-year incidence of chronic GVHD was 41%. There were 4 treatment-related deaths (1 from hepatic sinusoidal obstruction syndrome, 3 from early acute GVHD). In addition, 7 patients developed a noninfectious febrile syndrome shortly after transplant requiring prolonged courses of steroids. One-year overall and progression-free survival rates were 89% (95% confidence interval [CI], 74-96) and 76% (95% CI, 56-87), respectively. One-year cumulative incidences of relapse and nonrelapse mortality were 14% (95% CI, 4-29) and 11% (95% CI, 3-23), respectively. Circulating lymphocyte subsets were analyzed in 17 patients. Compared with controls, patients previously treated with PD-1 blockade had significantly decreased PD-1+ T cells and decreased ratios of T-regulatory cells to conventional CD4 and CD8 T cells. In conclusion, HSCT after PD-1 blockade appears feasible with a low rate of relapse. However, there may be an increased risk of early immune toxicity, which could reflect long-lasting immune alterations triggered by prior PD-1 blockade. •HSCT after PD-1 blockade is feasible, although may be associated with increased early immune toxicity.•PD-1 blockade may cause persistent depletion of PD1+ T cells and alterations in T-cell differentiation impacting subsequent treatment.